Entities of the Correlative Skills of Prospective Teachers Degree Students - Janusz Kirenko (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Solving the main research problem included in the question about the relationship between variables, dependent - prosocial skills, and independent, called subjective, in the dimensions of: assertiveness, coping in difficult situations and self-assessment, was tested using: Social Skills Questionnaire (KUS - AP Goldstein), Questionnaire of Assertiveness of the Teacher-Educator (KAN / W - T. Zubrzycka-Maciąg, J. Kirenko), COPE Questionnaire (COPE - CS Carver, MS Scheier, JK Weintraub) and the Self-Assessment Scale (SES - M. Rosenberg), 244 students of the faculties teachers, including 222 women (90.98%) and 22 men (9.02%). The age of the respondents ranged from 21 to 46 years, with an average of 25.29 years. They were students of pedagogy, English philology and pre-school and early school education from three universities in the Lublin region. A specific structure of compounds of selected variables was obtained, those that have a significant support in empiricum were highlighted. The applied multiple regression enabled the adoption of relatively precise characteristics of the compounds obtained, aspiring to be called autonomous applications.